Socio-Pedagogical Resilience in High-Risk Zones: Re-evaluating Community Policing Models for Safeguarding Child Rights in K-12 Educational Environment - Derese Simegnew Alehegn; R Karunakaran; Bantyergu Engida (Universitas Nahdlatul Ulama Surabaya, 2026)
Purpose: This study investigates the strategic re-evaluation of community policing as a mechanism for building socio-pedagogical resilience and safeguarding child rights within K-12 educational environments in high-risk zones. Methodology: This mixed-methods study utilized a descriptive research design, gathering quantitative survey data from 328 community members and front-line police, complemented by qualitative interviews with senior officials in Addis Ababa. Data analysis focused on assessing the implementation effectiveness and the correlation between policing partnerships and security outcomes. Findings: The results reveal that current community policing practices, with a grand mean of 2.564, are not yet fully effective in ensuring absolute safety. While obstacles such as trust issues, resource scarcity, and traditional beliefs regarding police-exclusive problem-solving hinder progress, statistical evidence confirms a significant positive relationship between community policing partnerships and the enhancement of safety within the educational ecosystem. The integrated partnership approach, bridging technical and local practical knowledge, explains the essential framework for fostering community ownership. Implications: The findings underscore the necessity of an integrated model that aligns security initiatives with inclusive educational policies to protect students. Recommendations: Future efforts should focus on strengthening collaborative frameworks between police, educational institutions, and the community to improve collective efficacy and student well-being. Originality/Value: Grounded in the necessity of social-institutional integration, this research provides empirical insight into how re-evaluating community policing models can serve as a vital safeguard for child rights and socio-pedagogical resilience in vulnerable environments.